Pencegahan Dini Kanker Payudara melalui Penyuluhan SADARI (Pemeriksaan Payudara Sendiri) pada Mahasiswi UNISKA Banjarbaru Tahun 2019 - Ridha Hayati; Hilda Irianty; Deni Suryanto (Jurnal Abdimas Kesehatan (JAK), 2020)
Breast Self-Examination (BSE) is an important step for early detection of breast cancer and should begin when a woman has menstruated, with a sensitivity / ability to detect around 20-30% (Nisman, 2011). The latest data on 31 January 2019, the breast cancer rate was 42.1 / 100,000 population with an average death rate of 17 / 100,000 population. Cases of breast cancer today are also commonly found at a young age, ranging from 15 years, 17, 19 years. This means that there has been a shift at a young age, possibly due to lifestyle, pollution, stress (Ministry of Health, 2019). BPMUB is an organization where students from various faculties and forums gather to conduct community activities, with a total of 55 members, and is a representative of 9 faculties in Uniska Banjarbaru, 45% of whom are women. Based on a questionnaire distributed to 25 BPMUB female members, 16 people knowledge of breast cancer were in the poor category, only 9 people were knowledgeable enough. In addition, awareness to do breast self-examination is still low, this is again due to lack of knowledge. The solution provided is awareness education for early detection of breast cancer, with a target audience of 50 people. The method used is lecture, demonstration and question and answer. The outputs of this service are publications in the Abdimas Health Journal, Baiturahim Jambi Stikes, publications on social media namely facebook and instagram as well as providing improved health values. Counseling was carried out on 17 December 2019 and evaluated on 6 January 2020, and the result of this activity was the real support from the Head of UPT UNISKA Banjarbaru and other faculty managers, enthusiasm from the target with attention and many questions both in activities and outside activities. Evaluation 2 weeks after socialization found 100% answered all questionnaires about BSE correctly. This means an increase in knowledge of the respondents. Socialization by providing these skills needs to be carried out continuously.